2020
DOI: 10.3390/microorganisms8060835
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Disease and Microbiome

Abstract: Gallstone disease (GSD) has, for many years, remained a high-cost, socially significant public health problem. Over the past decade, a number of studies have been carried out—both in humans and in animal models—confirming the role of the microbiota in various sections of the gastrointestinal tract as a new link in the etiopathogenesis of GSD. The microbiome of bile correlates with the bacterial composition of saliva, and the microbiome of the biliary tract has a high similarity with the microbiota of the duode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 130 publications
3
71
0
Order By: Relevance
“…Some studies denoted that there might be postoperative change of the microbiome. Change of microbial composition was observed in patients received cholecystectomy [ 29 , 30 ]. Gastrointestinal microbiota showed higher species diversity and richness after gastrectomy in patients with gastric cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies denoted that there might be postoperative change of the microbiome. Change of microbial composition was observed in patients received cholecystectomy [ 29 , 30 ]. Gastrointestinal microbiota showed higher species diversity and richness after gastrectomy in patients with gastric cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors suggest that Oscillospira may predispose individuals to cholesterol gallstones [ 5 ]. Cholecystectomy alters bile flow into the intestine and bidirectional interactions between bile acids and intestinal microbiota, thereby increasing bacterial degradation of bile acids into faecal secondary bile acids [ 104 , 105 ]. Deoxycholic acid can inhibit the growth of thececal microbiota in rats; moreover, members of the Bacteroidetes phylum ( Bacteroides vulgatus, Bacteroides sartorii ) are more sensitive to secondary bile acids exposure than members of the Firmicutes phylum ( Clostridium innocuum , Blautia coccoides ) [ 120 ].…”
Section: The Firmicutes/bacteroidetesratio and Gsdmentioning
confidence: 99%
“…Deoxycholic acid concentrations were negatively correlated with the Bacteroidetes phylum in patients with GSD [ 5 ]. Increasing levels of the cholic acid cause a dramatic shift toward the Firmicutes (from 54.1% before of administration of cholic acid up to 95% after [ 120 ]), particularly Clostridium cluster XIVa and increasing production of the harmful deoxycholic acid [ 104 , 121 ].…”
Section: The Firmicutes/bacteroidetesratio and Gsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota dysbiosis and bacterial community assembly were associated with cholesterol gallstones in a large-scale study [5][6][7]. It has been reported that the proportion of Lactobacillus is greatly reduced in CGS mouse models [8]; however, whether Lactobacillus supplementation can reduce gallstones has not been studied.…”
Section: Introductionmentioning
confidence: 99%